Yusuf Balasagwn and contribution to the Development historical medieval historical thought (Journal of history, 2020)
The article analyzes the work of Yusuf Balasagun «Kutadgu bilig». Showing the main ideas, words of wisdom writings is written in the form of dialogue and Elika Ugdulmisha. Сonsidering views Yusups on human qualities, education of the younger generation, dobrodotelstva, behavior, education, intelligence, understanding, right of kings and viceroys, palace servants and diplomats, generals and nokors, Derbishev and cooks, and others. Members of society. The author draws attention to the issues of progress and reform at the preservation of non-use of foundations suschestvenngo order, law-abiding, improving laws that Yu Balasagun emphasized in his work. Characterized views thinker of the main conditions of development of society, including those on education and science. Showing the foundations of spiritual purity, morality, and religion on the passages, which are taken from the work of the great thinker. Key words: Yusup Balasagun, «Kutadgu Bilig», the thinker, the state Karakhanids medieval historical thought, historiographical source, the idea of society, law, wisdom, wealth, progressive development of humanity, the religion of Islam.